Characteristics and risk factors of instrumentation failure following total en bloc spondylectomy. (1st February 2023) - Shimizu, Takaki; Kato, Satoshi; Demura, Satoru; Shinmura, Kazuya; Yokogawa, Noriaki; Kurokawa, Yuki; Yoshioka, Katsuhito; Murakami, Hideki; Kawahara, Norio; Tsuchiya, Hiroyuki
Abstract : Aims: The aim of this study was to investigate the incidence and characteristics of instrumentation failure (IF) after total en bloc spondylectomy (TES), and to analyze risk factors for IF. Methods: The medical records from 136 patients (65 male, 71 female) with a mean age of 52.7 years (14 to 80) who underwent TES were retrospectively reviewed. The mean follow-up period was 101 months (36 to 232). Analyzed factors included incidence of IF, age, sex, BMI, history of chemotherapy or radiotherapy, tumour histology (primary or metastasis; benign or malignant), surgical approach (posterior or combined), tumour location (thoracic or lumbar; junctional or non-junctional), number of resected vertebrae (single or multilevel), anterior resection line (disc-to-disc or intravertebra), type of bone graft (autograft or frozen autograft), cage subsidence (CS), and local alignment (LA). A survival analysis of the instrumentation was performed, and relationships between IF and other factors were investigated using the Cox regression model. Results: A total of 44 patients (32.4%) developed IF at a median of 31 months (interquartile range 23 to 74) following TES. Most IFs were rod fractures preceded by a mean CS of 6.1 mm (2 to 18) and LA kyphotic enhancement of 10.8° (-1 to 36). IF-free survival rates were 75.8% at five years and 56.9% at ten years. The interval from TES to IF peaked at two to three years postoperatively and continued to occur over a period of time thereafter; the early IF-developing group had greater CS at one month postoperatively (CS1M) and more lumbar TES. CS1M ≥ 3 mm and sole use of frozen autografts were identified as independent risk factors for IF. Conclusion: IF is a common complication following TES. We have demonstrated that robust spinal reconstruction preventing CS, and high-quality bone grafting are necessary for successful reconstruction. Cite this article: Bone Joint J  2023;105-B(2):172–179.